Work Motivation in Islam - Mahmud Yusuf (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to determine motivation from an Islamic perspective. This study uses a descriptive qualitative method, with a literature study approach. The results of this study are Islamic views that humans are built on the physical, mind, and spirit, all three of which must be fulfilled proportionally so that individual motives are built in a balanced way. A person will increase his work productivity and human work will be achieved optimally if his basic human needs are met properly both physical and spiritual needs. The conclusion of this research is, therefore, with the word of Allah SWT and the hadiths of the Prophet SAW that support halal jobs and the obligation to work with the intention of worship. Humans on earth, especially Muslims, must throw away the feeling of laziness. In addition, it must also increase motivation and high morale so that all work goals can be achieved to the maximum with the blessing of Allah SWT.